Turning Laminaria digitata seaweed into a resource for sustainable and ecological removal of trivalent chromium ions from aqueous solutions - Ingrid M. Dittert (2013)
This study presents the application of a safe, cost effective, environmental friendly, and efficient technology for the removal of trivalent chromium ions from aqueous solutions, based on the valorisation of a renewable resource, Laminaria digitata seaweed. Insights into trivalent chromium speciation in solution and interaction with the active sites present in the surface of the brown algae were studied. Carboxyl and hydroxyl groups were identified as the major binding sites present in the surface of the biosorbent, in concentrations (Q (max)) of 2.06 +/- A 0.01 and 1.4 +/- A 0.7 mmol g(-1), and with proton binding parameters (pK) of 3.28 +/- A 0.01 and 11 +/- A 1, respectively. Trivalent chromium uptake at equilibrium conditions was well described at different acidic pH conditions and chromium concentrations, using a model which incorporates trivalent chromium hydrolysis reactions in the aqueous phase and its chemical interactions with the available active sites (carboxyl groups) present in the surface of biosorbent. The distribution profile of trivalent chromium species present in the solution as well as at the binding sites indicated that Cr3+ and CrOH2+ exhibit different affinities for the carboxyl groups present in the surface of the biomass according to the pH. A mass transfer kinetics model was applied to describe the kinetics at batch system, being possible to obtain the distribution of CrOH2+ and Cr3+ species in solution and at the binding sites.